End-of-Charge Temperature Rise and State-of-Health Evaluation of Aged Lithium-Ion Battery - Binghong Han; Jonathon R. Harding; Johanna K. S. Goodman; Zhuhua Cai; Quinn C. Horn (Energies, 2022)
An increasing demand to repurpose used lithium-ion batteries in secondary applications is driving the need to develop methods of evaluating the state-of-health of used batteries. In this paper, we discover a self-terminated end-of-charge temperature rise (ECTR) phenomenon in 18650 lithium-ion cells, both recycled from the field and aged under controlled conditions in the lab. ECTR is characterized by an additional temperature rise near the end of the charging process and is accompanied by low coulombic efficiency. A higher charge rate and longer inactive time at low state-of-charge appear to increase the occurrence of ECTR. The intensity of ECTR is found to closely correlate with the excess charge capacity but is less affected by the charge current or cell impedance. ECTR is weakly dependent on the remaining cell capacity in recycled cells, and the controlled aging study shows that aging condition, not remaining capacity or internal resistance, determines the presence and intensity of ECTR behavior, which indicates that usable capacity or internal resistance should not be the single criterion to effectively evaluate the state-of-health of used cells intended for repurposing. We hypothesize that the origin of the ECTR is due to the formation of an internal lithium metal short that forms near the end of the charge process and self-terminates over time. The investigation of ECTR in this work provides a new criterion and approach to evaluate the state-of-health of cells required to safely handle aged/recycled cells.